Epidemiology of Vasculitides in Khorasan Province, Iran - Mohammadhassan Jokar; Zahra Mirfeizi (Iranian Journal of Medical Sciences, 2015)
Vasculitides are a heterogeneous group of more than 20 diseases defined by inflammation and destruction of blood vessels. We aimed to study the demographic characteristics of the primary vasculitides in the North East of Iran. We retrospectively studied the medical records of patients diagnosed with any kind of vasculitis at the Clinic and Department of Rheumatology of the Imam Reza Hospital, Mashhad, Iran between January 1, 2002, and December 31, 2012. Patients were classified according to the American College of Rheumatology 1990 criteria for the classification of vasculitis and the 2012 Revised International Chapel Hill Consensus Conference Nomenclature of Vasculitides. A total of 721 patients (51.5% male, 48.5% female) with a diagnosis of primary vasculitis was identified. The frequency distributions of vasculitic disorders were as follows: Behcet’s disease, 63.6%; cutaneous leukocytoclastic angiitis, 8.2%; granulomatosis with polyangiitis (Wegener’s), 6.8%; Takayasu’s arteritis. 6%; giant cell arteritis, 4%; polyarteritis nodosa, 2.1%; microscopic polyangiitis, 0.6%; eosinophilic granulomatosis with polyangiitis (Churg-Strauss), 1.8%; cryoglobulinemic vasculitis, 0.3%; and IgA vasculitis (Henoch-Schonlein purpura), 3.5%. In our population, the most common forms of vasculitis are Behcet’s disease, cutaneous leukocytoclastic angiitis, and granulomatosis with polyangiitis (Wegener’s).